(untitled) - Tortora, Gerard J. (New York, 2003)
A solid scientific presentation of the principles of the human structure and function! The outstanding illustration program and innovative learning features frame a superb balance between anatomy and physiology that emphasizes correlations between normal physiology and pathophysiology, normal anatomy and pathology, and homeostasis and homeostatic imbalances.
Keywords: Human physiology,Human anatomy